2008
DOI: 10.1002/pssa.200777793
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing Mueller matrices: how to decompose them?

Abstract: The various decompositions of depolarizing Mueller matrices into products of basic optical devices, i.e. retarders, diattenuators and depolarizers, are critically revisited and discussed. Both classic as well as recently proposed factorizations are reviewed. Physical and calculation aspects such as depolarization and matrix singularity are comparatively addressed. The problems of physical realizability and matrix filtering are treated in connection with the sum decomposition of a depolarizing Mueller matrix. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 20 publications
1
35
0
1
Order By: Relevance
“…It is noted that the order and the number of the equivalent elements in the decomposition models do have an influence in the interpreted depolarization, retardance and diattenuation properties [138]. Comparison studies of Lu-Chipman and reverse decomposition showed that these two methods yield consistent decomposition results providing that the magnitude of diattenuation of the medium is low [139].…”
Section: Factor Product Decompositionmentioning
confidence: 98%
“…It is noted that the order and the number of the equivalent elements in the decomposition models do have an influence in the interpreted depolarization, retardance and diattenuation properties [138]. Comparison studies of Lu-Chipman and reverse decomposition showed that these two methods yield consistent decomposition results providing that the magnitude of diattenuation of the medium is low [139].…”
Section: Factor Product Decompositionmentioning
confidence: 98%
“…Decomposition of Mueller matrices are well described in the literature as reviewed by Ossikovski et al [5]. Here we address sum decomposition of depolarizing Mueller matrices.…”
Section: Introductionmentioning
confidence: 94%
“…It has been shown that the other possible decompositions can be obtained from these two decompositions by using similarity transformations [66]. While, these two decomposition processes have been the most widely explored for analyzing tissue polarimetry signal, few other types of decomposition processes have also been proposed [67,68]. These include the symmetric decomposition developed by Ossikovski [67] and the sum decomposition, known as the Cloude decomposition [68].…”
Section: Quantitative Mueller Matrix Polarimetry Applied To Biomedicamentioning
confidence: 99%
“…While, these two decomposition processes have been the most widely explored for analyzing tissue polarimetry signal, few other types of decomposition processes have also been proposed [67,68]. These include the symmetric decomposition developed by Ossikovski [67] and the sum decomposition, known as the Cloude decomposition [68]. Nevertheless, once decomposed, the constituent 'basis' matrices are further analyzed to derive individual polarization medium properties, namely, linear retardance (δ, and its orientation angle θ), optical rotation (ψ), diattenuation (d) and depolarization coefficient (Δ) [33].…”
Section: Quantitative Mueller Matrix Polarimetry Applied To Biomedicamentioning
confidence: 99%